Microwave exposure induced ferroptosis by inhibiting the Nrf2 pathway and affected reproductive function in male mice - Jingchao Gao; Xinyue Li; Yizhuo Hou; Yanyang Li; Yueyue Pang; Xiaoran Wu; Li Zhao; Jing Zhang; Haoyu Wang; Hui Wang; Ji Dong; Xinping Xu; et al. (Ecotoxicology and Environmental Safety)
The mechanisms underlying the negative health effects of microwave exposure on male reproduction remain unclear. Thus, this study aimed to explore the role and regulatory mechanisms of ferroptosis in microwave-induced reproductive damage. The exposure of male C57 mice to 2.856 GHz of microwave radiation at 0, 10 and 20 mW/cm² for 30 min decreased sperm motility, induced morphological changes, damaged testicular tissue and mitochondrial morphology, increased malondialdehyde (MDA) contents and decreased the GSH/GSSG ratio. Simultaneously, the Fe²⁺ levels increased and SLC7A11 and GPX4 protein expressions decreased, causing oxidative stress. After 30 min of mouse spermatocyte (GC-2) irradiation, the cell viability of the Fer-1 inhibitor group and the GSH/GSSG ratio increased, while the reactive oxygen species, MDA and ferrous iron contents decreased. Furthermore, the depolarisation of membrane potential improved. Western blotting revealed that Nrf2, Keap1, SLC7A11, GPX4 and HO-1 expressions were down-regulated by microwave exposure and significantly up-regulated following the addition of the Fer-1 inhibitor. The results confirmed that the Nrf2 signalling pathway can regulate ferroptosis of oxidative stress. This study demonstrates that microwave exposure affects mouse reproductive function by enhancing oxidative stress, inducing ferroptosis by inhibiting the Nrf2 signalling pathway and reducing SLC7A11 and GPX4 protein expressions.